In-situ monitoring AHL-mediated quorum-sensing regulation of the initial phase of wastewater biofilm formation. (February 2020) - Wang, Jinfeng; Liu, Qiuju; Li, Xianhui; Ma, Sijia; Hu, Haidong; Wu, Bing; Zhang, Xu-xiang; Ren, Hongqiang
Graphical abstract: Highlights: Initial biofilm attachment was studied on-line and non-destructively. Reversible biofilm adhesion was identified in the initial attachment process. High concentration of AHLs shorten biofilm reversible adhesion process. The composition of QS-related bacteria was regulated by exogenous AHLs. Abstract: Initial attachment plays an important role in biofilm formation in wastewater treatment processes. However, the initial attachment process mediated by N-acyl-homoserine lactones (AHLs) is difficult to be fully understood due to the lack of non-invasive and on-line investigation techniques. In this study, the AHL-regulated wastewater biofilm attachment was quantified using ultrasonic time-domain reflectometry (UTDR) as an in-situ and non-invasive monitoring technique. Results demonstrated that the reversible adhesion time in municipal and industrial wastewaters was significantly decreased in the presence of exogenous AHLs. Biofilm thickness in municipal and industrial wastewaters increased significantly with the addition of exogenous AHLs. Also, the addition of acylase delayed the initial biofilm formation (lengthened reversible adhesion time and decreased biofilm thickness and density). Compared with biofilm behavior in the presence of low concentrations of AHLs (4.92 ± 0.17 μg/L), both reversible adhesion time and biofilm thickness were not significantly increased ( p > 0.05) with an increase in AHL concentration (9.75 ± 0.41 μg/L). Furthermore, the addition of exogenous AHLs resulted in significant changes in the attached bacterial community structures, in which both QS and quorum-quenching (QQ) bacteria were stimulated. The current work presents an effective approach to in-situ monitoring of the regulation of AHL-mediated QS in the initial attachment of biofilms, especially in the reversible adhesion process, which may provide a potential strategy to facilitate biofilm establishment in wastewater treatment processes.